Ambushes related to collecting patients’ consent for medical procedures by family doctors - Drobnik, Jarosław; Trnka, Jakub; Susło, Robert (Family Medicine & Primary Care Review, 2017)
A patient’s right to express consent – or lack thereof – to receive medical service is rooted primarily in the Polish Parliament’s Act on Patient’s Rights and Patient’s Rights Ombudsmen and in the Polish Parliament’s Act on the Professions of Physicians and Dentists. Performing a treatment procedure without previously collecting valid consent is a crime, resulting in criminal prosecution as severe as up to 2 years in prison. Collecting a patient’s consent to be subjected to medical service can be divided into four main phases: checking if consent shall be collected under current circumstances; determining from whom it shall be collected; passing information to the patient or other person entitled to receive it; and actual collection of consent from the person entitled to express it. Each of these can present as a potential ambush for physicians on multiple levels. Consent forms include: contextual, oral and written; and oral consent is quite often questioned by patients, as it is difficult to properly document the details of communication between the physician and patient during a visit. As consent for participation in a medical experiment always requires a written form preceded by passing on relevant information to the patient; it is worth remembering that, according to some interpretations, prescribing drugs off-label to a patent by a physician fits the broad definition of therapeutic experiment. In the context of a patient’s consent to receive medical services, the rising need for documenting in medical files not only the patient’s final decision, but quite often also many physiciandependent factors as subsequent steps that led the patient to reaching this decision, is noticeably rising.